BIBLIOMETRIC ANALYSIS OF RESEARCH JOURNAL OF PHARMACY AND TECHNOLOGY (2008- 2012) - Wathore, Aknath R.; Pawar, Ganpat R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Analyse research papers published in the “RJPT” journal for five years from 2008 to 2013. Examines year-wise distribution of publications, issue-wise distribution of articles, authorship pattern, degree of collaboration, and geographical distribution of articles. The data for the present study was obtained from the journal archive’s official website RJPT. The retrieved data was analyzed to understand the pattern of authorship, degree of collaboration, and region-wise distribution of authors. The study revealed that most contributions were from India, particularly Maharashtra and Tamil Nadu.